Relation of Renal Dysfunction to Quality of Anticoagulation Control in Patients with Atrial Fibrillation: The FANTASIIA Registry - Esteve-Pastor, María Asunción; Rivera-Caravaca, José Miguel; Roldán-Rabadán, Inmaculada; Roldán, Vanessa; Muñiz, Javier; Raña-Míguez, Paula; Ruiz-Ortiz, Martín; Cequier, Ángel; Bertomeu-Martínez, Vicente; Badimón, Lina; Anguita, Manuel; Lip, Gregory Y. H.; Marín, Francisco; on behalf of FANTASIIA Study Investigators (Thrombosis and Haemostasis, 2018)
Background One-third of atrial fibrillation (AF) patients have chronic kidney disease (CKD), a condition that itself increases thromboembolic and major bleeding risks, especially in patients with severe CKD. Bleeding would be accentuated by suboptimal anticoagulation control with vitamin K antagonists (VKA).Purpose This article aimed to investigate the incidence of cardiovascular events, mortality and quality of anticoagulation in relation to CKD in a ‘real-world’ prospective cohort of AF patients included in the FANTASIIA registry.Methods We analysed consecutive AF patients who were prospectively recruited with a year of follow-up. The quality of anticoagulation was estimated by time in therapeutic range (TTR). The annual incidence of events was analysed.Results We studied 1,936 patients (male: 55.7%, mean: 73.8 ± 9.4 years): 445 (22.9%) had normal function, 698 (36.1%) had mild CKD, 713 (36.8%) had moderate CKD and 80 (4.2%) had severe CKD. Patients with estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m2 (severe CKD) had lower TTR (53.3 ± 25.6% vs. 61.8 ± 25.1%, p = 0.007) and higher proportion of poor TTR (67.2 vs. 51.8%; p = 0.014) than patients with eGFR ≥30 mL/min/1.73 m2. Severe CKD was significantly associated with cardiovascular mortality (hazard ratio [HR]: 9.33; p = 0.002), major bleeding (HR: 2.94; p = 0.036) and major adverse cardiovascular events (MACE) (HR: 4.93; p = 0.004). Importantly, 375 patients (21.1%) showed a deteriorating eGFR of ≥10 mL/min during the follow-up, with significantly higher mortality and cardiovascular events.Conclusion In a prospective and real-world AF registry, approximately 67% of patients with severe CKD had poor anticoagulation control while taking VKA. The presence of severe CKD was an independent factor for cardiovascular mortality, MACE and major bleeding. Worsening eGFR of only ≥10 mL/min during follow-up was significantly associated with mortality and major bleeding.
Keywords: chronic kidney disease; renal function; atrial fibrillation; vitamin K antagonists; time in therapeutic range; acenocoumarol